Issues surrounding HPV vaccine delivery in a multi-ethnic country in Asia: the physician's perspective - Wong, Li Ping (Springer, 2011)
The study was conducted to investigate issues surrounding human papillomavirus (HPV) vaccine delivery in a multi-ethnic, multi-religious and multi-cultural society. A qualitative in-depth interview study was conducted with a sample of 20 physicians. Physicians described the success of HPV vaccines recommendation as very poor. Many expressed reluctance to offer the vaccine to preadolescents. The most notable barrier to vaccination was the vaccine's high cost. Parents of eligible vaccinees were concerned about the efficacy and side effects of the new vaccine, while adult women have low risk perception for HPV infection. Promoters and inhibitors of HPV vaccination in our multi-ethnic, multi-religious and multi-cultural community were identified. This study suggests the need to strengthen the infrastructure necessary for HPV vaccine delivery and to specifically target poor underserved women.